Socratic Seminars as a Tool for Inductive Learning - Feldgen, María; Clúa, Osvadlo (Anais do Workshop sobre Educação em Computação (WEI); 2009: Anais do XVII Workshop sobre Educação em Computação, 2009)
Teaching a course with cross disciplinary graduated students is a tradeoff between an overview and a technical approach. The inclusion of Distributed Systems in a postgraduate specialization course in telecommunications is an example. As the specialization course is focused in the management aspects, we decided to use an inductive learning approach using Socratic Seminars to elicit their participation. Socratic Seminars prevent students from adopting a surface learning approach. The seminars give an opportunity to deep oriented students to relate the course materials with their own interests. In our experience, some of the surface learners became enthusiastic when saw the deep learners performance.